Scientific evidence on the use of recombinant human bone morphogenetic protein-2 (rhBMP-2) in oral and maxillofacial surgery - Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Okamoto, Roberta [UNESP]; Ferreira, Sabrina [UNESP]; De Oliveira, Danila [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Faverani, Leonardo Perez [UNESP] (Springer Nature, 2016)
Purpose: This study aimed to identify the main indications for the use of recombinant human bone morphogenetic protein-2 (rhBMP-2) for bone repair and maintenance in the maxilla and mandible through a review of clinical trials evaluating the viability of using rhBMP-2 to delay the installation of dental implants, thus allowing satisfactory bone formation and long-term osseointegration. Methods: Literature search of the PubMed/Medline databases was performed using the following MeSH index terms—“bone morphogenetic protein 2” and “dentistry”. Only clinical trials necessarily published in English, related to dentistry, and focused on bone reconstruction in critical defects, post-extraction alveoli, increasing the atrophic alveolar ridge, or surgery for maxillary sinus elevation were included, regardless of the age, sex, ethnicity, associated morbidities, or period of publication. Results: Of the 17 studies identified based on the search filters, 2 were excluded. Therefore, 15 studies were finally included in this review. Conclusions: Based on the results of our review, we concluded that the use of rhBMP-2 for the preservation of the alveolar ridge after tooth extraction or for increasing the local defects is safe and viable. The use of rhBMP-2/Bio-Oss® for the elevation of the maxillary sinus membrane is unnecessary; however, it can improve and accelerate the maturation process in cases of guided bone regeneration in peri-implant defects. Compounds comprising rhBMP-2, allogenic bone, and plasma-rich platelet (PRP) can act as autograft substitutes in mandibular critical defects.
Keywords: Atrophy; Biocompatible materials; Bone morphogenetic protein 2; Bone regeneration